Attaining semi-quantitative SERS measurements on thermally dewetted Au films. (2nd October 2017) - Andrikaki, S.; Govatsi, K.; Yannopoulos, S. N.; Voyiatzis, G. A.; Andrikopoulos, K. S.
Abstract: The current work attempts to provide a proof of concept for the achievement of semi-quantitative measurements by applying Surface Enhanced Raman Scattering (SERS) on thermally dewetted Au-films. In order to probe the anticipated advanced (device) material, Mitoxantrone (MTX) that exhibits strong SERS signal was utilized as a relevant prototype active molecular agent. The molecule was deposited on substrates of different morphology by spin coating and after evaluation of the collected SERS spectra it is shown that there is an almost linear correlation between the SERS intensity and the concentration of the SERS active molecule. In addition the enhancements achieved depend on the substrate's morphology.